2021
DOI: 10.3389/fsufs.2021.684434
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest UV-C Irradiation Influenced Cellular Structure, Jasmonic Acid Accumulation, and Resistance Against Green Mold Decay in Satsuma Mandarin Fruit (Citrus unshiu)

Abstract: Green mold caused by Penicillium digitatum is an important factor limiting the shelf life of mandarin fruit. In this study, the effect of ultraviolet-C (UV-C) irradiation on cellular structure, endogenous jasmonic acid (JA), and development of P. digitatum in satsuma mandarin fruit was investigated. UV-C treatments included 0 (untreated control), 3, and 10 kJ m−2 or the exposure time of 0, 1.18, and 4.52 min, respectively. The UV-C dose of 10 kJ m−2 significantly reduced the development of P. digitatum both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
3
0
3
Order By: Relevance
“…In cold-stored citrus fruits, induced resistance was linked to the build-up of phytoalexins, such as scopoletin and scoparone [56]. Phonyiam et al [65] demonstrated that application of UV-C at 10 kJ m −2 on Satsuma mandarins was able to reduce the growth of P. digitatum (green mould), maintaining the integrity of the membrane structure by reducing lipid peroxidation and increasing jasmonic acid accumulation with the induction of bioactive compounds and the antioxidant potential of DPPH radical scavenging capacity. Yamaga et al [50] showed that low UV-B doses (15 kJ m −2 ) had an inhibitory effect on P. italicum growth in vitro, with a reduction in spore germination >99%.…”
Section: Irradiationmentioning
confidence: 99%
“…In cold-stored citrus fruits, induced resistance was linked to the build-up of phytoalexins, such as scopoletin and scoparone [56]. Phonyiam et al [65] demonstrated that application of UV-C at 10 kJ m −2 on Satsuma mandarins was able to reduce the growth of P. digitatum (green mould), maintaining the integrity of the membrane structure by reducing lipid peroxidation and increasing jasmonic acid accumulation with the induction of bioactive compounds and the antioxidant potential of DPPH radical scavenging capacity. Yamaga et al [50] showed that low UV-B doses (15 kJ m −2 ) had an inhibitory effect on P. italicum growth in vitro, with a reduction in spore germination >99%.…”
Section: Irradiationmentioning
confidence: 99%
“…Given the phenotype of inhibited fungal growth severity in UV-B treated fruits Figs. (1 and 2), it could be postulated that UV-B light (and UV-C) elevates plants' resistance by urging them to accumulate several defense-related molecules such as jasmonic acid and its derivatives (Escobar Bravo et al, 2019;Phonyiam et al, 2021;Qi et al, 2018). Recently, (Li et al, 2022) reported that B. cinerea infection in sweet cherry could be controlled through the activation of jasmonic acid biosynthesis in response to Mushroom volatile alcohol (also called 1-octen-3-ol).…”
Section: A B Discussionmentioning
confidence: 99%
“…The resistance to the pathogen has been attributed to the accumulation of phytoalexins such as scoparone and scopoletin [37,38]. Phonyiam et al [39] showed that application of a UV-C dose of 10 kJ m -2 on Satsuma mandarins was able to reduce green mold growth due to increased accumulation of jasmonic acid and bioactive compounds with high antioxidant activity. They also reported a reduction in lipid peroxidation, which helped maintain the integrity of the membrane structure.…”
Section: Preliminary Irradiation Test On Lemonsmentioning
confidence: 99%